PENYELESAIAN SENGKETA PERBANKAN SYARIAH (ANALISIS YURIDIS PUTUSAN VERSTEK PENGADILAN AGAMA PALU PERKARA NOMOR 510/Pdt.G/2020/PA.Pal) - Hayati, Nur; Fitria, Norma; Faruq, Ahmad (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2022)
Abstract: This research includes the Juridical Analysis of Verstek Decisions of the Palu Religious Court Case Number 510/Pdt.G/2020/PA.Pal. analyzing dispute resolution in the Verstek Decision case number 510/Pdt.G/2020/PA.Pal. has two data sources, namely primary data and secondary data. After all the data was collected, the researcher then analyzed using the normative juridical approach. the existence of a sharia banking dispute resolution in a breach of contract/broke of promise to the Bri Syariah Bank to the defendant (kifran) and it was decided in a Verstek manner because the Defendant was not present at the trial even though he had been properly summoned by the Palu Religious Court. Keywords: Sharia Banking Disputes, Juridical Analysis of Verstek Decisions, Religious Courts.